Child Support and Young Children's Development - Nepomnyaschy, Lenna (2012)
This study examines the effects of nonresident fathers’ provision of formal and informal cash child support on children's cognitive skills and behavior at 5 years of age. Taking advantage of the panel structure of the Fragile Families and Child Wellbeing Study, we control for child outcomes at age 3 and a rich set of child and family sociodemographic and psychosocial characteristics. We find that fathers’ provision of informal cash support (but not formal support), particularly at or above the median, is associated with higher cognitive scores. We also find that provision of formal child support is associated with worse withdrawn and aggressive behaviors. We discuss potential explanations and implications of these results for policy and future research.